Case Report: The effect of automated manual lymphatic drainage therapy on lymphatic contractility in 4 distinct cases - Aldrich, Melissa B.; Rasmussen, John C.; Karni, Ron J.; Fife, Caroline E.; Aviles, Frank; Eckert, Kristen A.; Melin, M. Mark (Frontiers in Medical Technology, 2024)
Introduction Automated manual lymphatic drainage therapy (AMLDT) is available for home use in the form of a pneumatic mat of 16 pressurized air channels that inflate and deflate to mimic the stretch and release action of manual lymphatic drainage therapy. Four cases (a patient with complex regional pain syndrome and lymphedema, a healthy patient, a breast cancer survivor with chronic pain, and a patient with a history of abdominal surgery) underwent near-infrared fluorescence lymphatic imaging (NIRFLI) with AMLDT to evaluate the effect of AMLDT on lymphatic pumping and pain. Methods Each patient received 32–36 injections of 25 μg indocyanine green (ICG) on the anterior and posterior sides of their body and underwent 1 h of NIRFLI to assess the drainage of ICG laden lymph toward regional nodal basins at baseline. Each patient lay supine on the mat for 1 h of AMLDT with NIRFLI to assess lymphatic flow during treatment. A final NIFRFLI assessment was done 30–60 min posttreatment with the patient in the supine and prone position. Patients reported baseline and posttreatment pain using the Visual Analogue Scale. An imager analyzed NIRFLI images using ImageJ (US National Institutes of Health). Using time stamps of the first and last images to determine time lapsed and the number of pulses observed in a timeframe, pulsing frequency (pulses/min) was obtained to assess lymphatic function. Results All 4 cases completed the NIRFLI and AMLDT without complications; all 3 patients with baseline pain reported reduced pain posttreatment. AMLDT appeared to alter lymphatic contractility, with both increased and decreased pulsing frequencies observed, including in nonaffected limbs. Pulsing frequencies were very heterogeneous among patients and varied within anatomic regions of the same patient. Discussion This proof-of-concept study suggests that AMLDT may impact lymphatic contractility. Further research on its effect on lymphatic function is warranted.